2022
DOI: 10.1007/s10460-022-10297-3
|View full text |Cite
|
Sign up to set email alerts
|

Decolonizing agriculture in the United States: Centering the knowledges of women and people of color to support relational farming practices

Abstract: While the agricultural knowledges and practices of Black, Indigenous, and People of Color (BIPOC) and women have shaped agriculture in the US, these knowledges have been colonized, exploited, and appropriated, cleaving space for the presently dominant white male agricultural narrative. Simultaneously, these knowledges and practices have been transformed to fit within a society that values individualism, production, efficiency, and profit. The authors use a decolonial Feminist Political Ecology framework to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…We encourage any college with an on-campus farm to evaluate the narrative around its farm, promoting it as an educational and rewarding endeavor that contributes to personal growth and community welfare (Alkon & Agyeman, 2011;Hoey et al, 2018). Further research and practical interventions are warranted to solidify the transformative potential of on-campus farming experiences (Layman & Civita, 2022;Sager et al, 2022aSager et al, , 2022b. Recognizing the diverse perspectives and experiences of participants can lead to a comprehensive understanding of the challenges and opportunities in on-campus farming, guiding future initiatives toward a more inclusive and effective model (Emery & Flora, 2006;Mathie & Cunningham, 2003;Sweeney et al, 2015).…”
Section: Potential Solutionsmentioning
confidence: 99%
“…We encourage any college with an on-campus farm to evaluate the narrative around its farm, promoting it as an educational and rewarding endeavor that contributes to personal growth and community welfare (Alkon & Agyeman, 2011;Hoey et al, 2018). Further research and practical interventions are warranted to solidify the transformative potential of on-campus farming experiences (Layman & Civita, 2022;Sager et al, 2022aSager et al, , 2022b. Recognizing the diverse perspectives and experiences of participants can lead to a comprehensive understanding of the challenges and opportunities in on-campus farming, guiding future initiatives toward a more inclusive and effective model (Emery & Flora, 2006;Mathie & Cunningham, 2003;Sweeney et al, 2015).…”
Section: Potential Solutionsmentioning
confidence: 99%
“…Experiences of racism are associated with distrust of agriculture-related government agencies (Balvanz et al, 2011) and avoidance of community participation (Medel-Herrero et al, 2021) among BIPOC farmers and farm workers. The appropriation of traditional BIPOC agricultural knowledge is another insidious form of racism (Layman & Civita, 2022).…”
Section: Farmer Stress and Mental Healthmentioning
confidence: 99%
“…The 2017 Census of Agriculture reported that 95% of U.S. farm producers are white (U.S. Department of Agriculture National Agricultural Statistics Service [USDA NASS], 2017), and farming is generally taught and understood through a colonial lens (Layman & Civita, 2022). Practices such as regenerative agriculture promote systems that can heal the land, but still often exclude Indig-1 I use the term "peasant" farmer to refer to a person of the land, who has a direct and special relationship with the land.…”
Section: Introductionmentioning
confidence: 99%